Glycogenic acanthosis of the tongue - Suhasini P. Gotur; Nagaraju Kamarthi; Vijay Wadhwan (Wolters Kluwer Medknow Publications, 2024)
Glycogenic acanthosis (GA) is a benign lesion characterized by elevated, small, white plaques commonly detected in the esophageal mucosa. To date, only 6 cases have been reported in the English literature documenting its involvement in the oral cavity. Herein we report a case of large GA on the ventrolateral aspect of the tongue in a 42-year-old male (third case reported on the tongue). Histologically, the lesion was characterized by acanthotic squamous epithelium with glycogen-rich, clear cells located in the upper layers of the epithelium. Since the oral presentation of GA is very rare, it is necessary to document more cases to clarify the clinical features, biological behavior, and management of GA in the future.